(untitled) (Kinesiology, 2020)
This study was designed to assess the ability of the Talk Test (TT) to track training-related changes in ventilatory threshold (VT). Thirteen recreational athletes (mean±SD; age, 20.5±1.91 years, (Males=7, Females=6) completed two incremental exercise tests (one with respiratory gas exchange and one with the TT) before and after 6-weeks of self-directed increases in training load. The TT was used to predict VT by assessing the ability to speak comfortably after 3-minute exercise stages based on speech comfort during a 100-word passage. Training load was documented using exercise logs based on sRPE and training duration. Repeated measures ANOVA, with Tukey’s post-hoc analysis, was used to detect differences between the changes in power output at the equivocal stage of the Talk Test and VT measured by gas exchange (p<.05). Significant mean differences were found between pre vs post training power output at the equivocal stage of the Talk Test (125+40.8 vs 135+29.8 Watts) and measured VT (116+32.4 vs 134+32.4 Watts) (p>.05). However, the increase in power output at VT (+15.5%) was significantly underestimated by the change in power output at equivocal stage of the TT (+8.0%). The correlation between changes in power output at VT and PO at the equivocal stage of the TT was r=0.66. However, about 50% of subjects did not change their power output at the equivocal stage of the TT, so the individual correspondence between Talk Test and measured VT was only moderately strong.